Temporal Trends, Characteristics, and Outcomes of Infective Endocarditis After Transcatheter Aortic Valve Replacement. (18th March 2021) - del Val, David; Abdel-Wahab, Mohamed; Linke, Axel; Durand, Eric; Ihlemann, Nikolaj; Urena, Marina; Pellegrini, Costanza; Giannini, Francesco; Landt, Martin; Auffret, Vincent; Sinning, Jan Malte; Cheema, Asim; et al.
Abstract: Background: Procedural improvements combined with the contemporary clinical profile of patients undergoing transcatheter aortic valve replacement (TAVR) may have influenced the incidence and outcomes of infective endocarditis (IE) following TAVR. We aimed to determine the temporal trends, characteristics, and outcomes of IE post-TAVR. Methods: Observational study including 552 patients presenting definite IE post-TAVR. Patients were divided in 2 groups according to the timing of TAVR (historical cohort [HC]: before 2014; contemporary cohort [CC]: after 2014). Results: Overall incidence rates of IE were similar in both cohorts (CC vs HC: 5.45 vs 6.52 per 1000 person-years; P = .12), but the rate of early IE was lower in the CC (2.29‰ vs 4.89‰, P < .001). Enterococci were the most frequent microorganism. Most patients presented complicated IE ( CC: 67.7%; HC: 69.6%; P = .66), but the rate of surgical treatment remained low (CC: 20.7%; HC: 17.3%; P = .32). The CC exhibited lower rates of in-hospital acute kidney injury (35.1% vs 44.6%; P = .036) and in-hospital (26.6% vs 36.4%; P = .016) and 1-year (37.8% vs 53.5%; P < .001) mortality. Higher logistic EuroScore, Staphylococcus aureus etiology, and complications (stroke, heart failure, and acute renal failure) were associated with in-hospital mortality in multivariable analyses ( P < .05 for all). Conclusions: Although overall IE incidence has remained stable, the incidence of early IE has declined in recent years. The microorganism, high rate of complications, and very low rate of surgical treatment remained similar. In-hospital and 1-year mortality rates were high but progressively decreased over time. Abstract : Incidence rates of infective endocarditis following transcatheter aortic valve replacement were similar in both cohorts (historical cohort: before 2014; contemporary cohort: after 2014) and the rate of early infective endocarditis significantly declined in recent years. Microbiological profile and rate of in-hospital complications were similar in both cohorts. In-hospital and 1-year mortality showed a decreasing temporal trend in this population.